SISTEM PENDUKUNG KEPUTUSAN EVALUASI KINERJA PEGAWAI UNTUK PENENTUAN REWARD AND PUNISHMENT DI PEMERINTAH KABUPATEN SRAGEN - , Bekti Nugroho ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Qualified personnel will facilitate the work unit to achieve its goals. To encourage employees to work better, then the unit can provide rewards to employees who are considered outstanding and provide sanctions for employees who are lazy. But in determining who is an employee who is lazy or diligent often have difficulty because of the absence of accurate measuring devices. In this study developed a decision support system for assessing the environmental performance of civil servants in Sragen regency government for the determination of reward and punishment. In the process of determining the value of employee performance, use of the work targets of individual employees. Determination of value is determined based on the results of joint deliberation. In the evaluation of employee performance can be made monthly and annual. With the decision support system is expected officials will not have difficulty in selecting the employees who deserve to be rewarded as well as employees who deserve to be sanctioned. Employees are expected to further improve performance and the spirit in the work.